Species diversity of yeast in oral colonization of insulin-treated diabetes mellitus patients - Helena Pires Goncalves, Regina; Miranda, Elaine Toscano; Zaia, Jose Eduardo; Mendes-Giannini, Maria José Soares [UNESP] (Springer, 2006)
The aim of this study was to investigate oral yeast colonization, antifungal susceptibility and strain diversity in insulin-dependent diabetes mellitus patients (175), as well as to evaluate the influence of dental prostheses. Oral rinse samples were cultured on selective media, in order to isolate, count and identify the yeasts recovered. More than half of the diabetic subjects (53%) carried significant amounts of Candida cells in the buccal cavity and these organisms were recovered at higher densities in diabetics wearing dentures. A total of 93 yeast strains were isolated from these patients, including: Candida spp. (n = 89); Pichia (n = 02); Trichosporon (n = 1), and Geotrichum (n = 1). C. albicans represented 56% of these strains, non-albicans Candida 39.8%, and other genera of yeast 4.3%. C. albicans was prevalent, followed by C. parapsilosis, C. tropicalis, C. glabrata, C. krusei, C. rugosa and C. guilliermondii. Agar disk-diffusion tests of the susceptibility of non-albicans Candida and other genera of yeast to fluconazole showed resistance in 21.9%, mainly in C. rugosa (100%), C. glabrata (57%) and C. krusei (50%). Local oral factors, such as the presence of dentures, in association with diabetes, seemed to have the effect of increasing the amount and variety of Candida species in the oral cavities, mainly those with lower drug susceptibilities.
Keywords: Candida spp; diabetes mellitus; disk diffusion; prostheses; oral carriage